2015
DOI: 10.1074/jbc.m115.654483
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Core 1-derived O-Glycans Decreases Breast Cancer Development in Mice

Abstract: Background: Abnormal mucin-type O-glycosylation is in human breast cancer tissues with unclear in vivo functions. Results: Core 1 ␤1,3-galactosyltransferase (C1galt1) is critical to O-glycosylation. Genetic deletion of C1galt1 in the mammary epithelium reduces tumor development in breast tumor mouse models. Conclusion: Lacking core 1-derived O-glycans retards breast cancer development in mice. Significance: Core 1-derived O-glycans are important during mammary tumorigenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…Up-regulated C1GALT1 is associated more with mCRPC than with localized tumors, which suggests that core 1 O-glycosylation may mediate the dissemination and adaptation of cancer cells to distant tissues. In line with this supposition, genetic deletion of C1galt1 in the mammary epithelium hampered carcinogenesis in the MMTV-PyMT mouse mammary tumor model (39). In colorectal tumors, increased C1GALT1 expression was associated with poor survival, whereas C1GALT1 overexpression modified O-glycans on fibroblast growth factor receptor 2 and enhances its phosphorylation, which promotes invasive behavior and stem-like properties in colon cancer cells (40).…”
Section: Discussionmentioning
confidence: 84%
“…Up-regulated C1GALT1 is associated more with mCRPC than with localized tumors, which suggests that core 1 O-glycosylation may mediate the dissemination and adaptation of cancer cells to distant tissues. In line with this supposition, genetic deletion of C1galt1 in the mammary epithelium hampered carcinogenesis in the MMTV-PyMT mouse mammary tumor model (39). In colorectal tumors, increased C1GALT1 expression was associated with poor survival, whereas C1GALT1 overexpression modified O-glycans on fibroblast growth factor receptor 2 and enhances its phosphorylation, which promotes invasive behavior and stem-like properties in colon cancer cells (40).…”
Section: Discussionmentioning
confidence: 84%
“…These types of defects are indeed observed in some colon, blood, and pancreatic cancers (Ju et al, 2008;Mi et al, 2012). However, experimentally depleting C1GALT1 yields limited effects or reductions in tumor growth in various systems (Radhakrishnan et al, 2014;Song et al, 2015).…”
Section: Discussionmentioning
confidence: 96%
“…Conversely, Bergstrom and colleagues unexpectedly found that Tn antigen is not involved with cancer progression in a murine model of colorectal cancer; instead intestinal inflammation is a major mechanism responsible for tumour development . Song et al even reported that Tn antigen expression suppressed breast cancer development in mice via impairment of MUC1 expression, which is usually highly expressed in various cancers . All of these findings suggest that the role of Tn antigen in cancer progression and metastasis needs to be further understood.…”
Section: Discussionmentioning
confidence: 99%
“…37 Song et al even reported that Tn antigen expression suppressed breast cancer development in mice via impairment of MUC1 expression, which is usually highly expressed in various cancers. 38 All of these findings suggest that the role of Tn antigen in cancer progression and metastasis needs to be further understood.…”
Section: Discussionmentioning
confidence: 99%